2005
DOI: 10.1136/bjo.2005.067306
|View full text |Cite
|
Sign up to set email alerts
|

Improving the repeatability of Heidelberg retina tomograph and Heidelberg retina tomograph II rim area measurements

Abstract: Aims: To devise and test strategies for improving Heidelberg retina tomograph (HRT and HRT-II) rim area (RA) repeatability and assess the benefit of the strategies in time series of HRT images. Methods: The effect of the standard and 320 mm reference planes and image quality on RA repeatability was assessed in a test-retest HRT image dataset from 74 subjects. A longitudinal HRT image dataset from 30 ocular hypertensive subjects was analysed by linear regression of RA over time, with each of the reference plane… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
32
0
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(36 citation statements)
references
References 25 publications
3
32
0
1
Order By: Relevance
“…22,[37][38][39][40][41] While this may be correct in a slowly progressive condition like glaucoma, our findings in papilledema shows substantial deformations of the peripapillary RPE/BM, in some cases over short time intervals, relative to other surface and subsurface regions of the optic disc. There may be limits to the use of the RPE/BM as a reference plane in patients with intracranial hypertension.…”
Section: Discussionmentioning
confidence: 81%
“…22,[37][38][39][40][41] While this may be correct in a slowly progressive condition like glaucoma, our findings in papilledema shows substantial deformations of the peripapillary RPE/BM, in some cases over short time intervals, relative to other surface and subsurface regions of the optic disc. There may be limits to the use of the RPE/BM as a reference plane in patients with intracranial hypertension.…”
Section: Discussionmentioning
confidence: 81%
“…A manual alignment facility was used to correct contour line position if the automatically placed contour line was misplaced or if there was a magnification change. 17 When a satisfactory contour line position could not be achieved, the mean topography was excluded from the analysis. Eight mean topographies were excluded from the analysis, as a result either of a double image being present or if the image was so grainy as to preclude visualization of Elschnig's ring.…”
Section: Hrt Analysismentioning
confidence: 99%
“…The use of disc photographs in plotting the contours has been used selectively in studies, and other studies have not used them in defining the contours. [11][12][13] Furthermore, there is little literature that directly compares the results on whether it is truly beneficial. Spencer et al 14 showed that HRT measurements for the vertical optic disc diameter were significantly smaller compared with the measurements taken on optic disc photographs.…”
Section: Discussionmentioning
confidence: 97%